An introduction to historical bibliography - Binns, Norman E. (London : Association of Assistant Librarians, 1962)
The origin and development of the alphabet. The modern alphabet is the result of successive developments which began almost as soon as man could speak and earliest were pictures of objects and ideas or thoughts
Includes bibliographies.
obn 21/01/2019
Loans
Keywords: Books; Printing